VARIABEL ANTESEDEN KUALITAS LAPORAN KEUANGAN DANA BOS DENGAN REGULASI PEMERINTAH SEBAGAI PEMODERASI - riana (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
The main purpose of this study was to determine the effect of the variable on the quality of the financial statements of BOS funds with Government Regulations as moderating. The population of this research is the State Vocational High School (SMKN) that receives BOS funds within the DKI Jakarta Provincial Education Office and the number of samples from this study is 73 public vocational schools. Analysis to test data and hypotheses was carried out using Moderated Regression Analysis (MRA) with SPSS version 26 program. The results of this study are as follows. First, the Accounting Information System has a direct and significant effect on the Quality of the Financial Statements of BOS funds. Second, the Internal Control System has a direct and significant effect on the Quality of the Financial Statements of BOS funds. Third, Human Resources Competence has no direct and insignificant effect on the Quality of Financial Statements of BOS funds. Fourth, Indirectly, Government Regulations in Accounting Information Systems have no and no significant effect on the Quality of Financial Statements of BOS funds. Fifth Indirectly, Government Regulations in the Internal Control System are influential and significant. Sixth, Indirectly, Government Regulations in HR Competency have no and no significant effect on the Quality of Financial Statements of BOS funds.